金属带式CVT钢带轴向跑偏电液控制系统的仿真 - 臧发业; 张玉波 (Jixie chuandong)
On the basis of the analysis of the belt misalignment of the metal V-belt CVT,the reason of the belt misalignment is discussed.In order to control the misalignment,an electro-hydraulic control system is designed.After analyzing the structure and principle of the electro-hydraulic control system,the mathematical model of the electro-hydraulic control system is established.Being varieties of the working situation of car and the non-linearity of the electro-hydraulic control system,a fuzzy PID algorithm is adopted.Then the performance simulation of the electro-hydraulic control system is conducted.The simulation results showe that the electro-hydraulic control system and the fuzzy controller with parameter self adjustment could not only control ratio,which has a higher accuracy of the stable state and a stronger robust of the driving condition,but also eliminate the belt misalignment.